Recurrent bloodstream infections after allogeneic hematopoietic cell transplantation. Issue 1 (2nd January 2023) - Akhmedov, Mobil; Klyasova, Galina; Kuzmina, Larisa; Parovichnikova, Elena
ABSTRACT: Background: Although colonization is an established risk factor for bloodstream infection (BSI) due to identical strain, prior infection with resistant bacteria should also be considered during the management of febrile neutropenia. This study aimed to analyze the rate and etiology of recurrent BSI in allogeneic hematopoietic cell transplant (allo-HCT) recipients to determine its potential impact on decision-making. Materials and methods: The retrospective study included 284 allo-HCT recipients. Recurrent BSI was defined as a new BSI episode occurring in a period of more than 72 hours after antibiotic withdrawal. Results: Overall, 104 patients (36.6%) developed at least one BSI, and 23 of them (22.1%) experienced recurrent BSI episodes (n = 30). Median time to recurrent BSI was 41 days (range 5–526 days). Recurrent BSI was associated with second allo-HCT (p < 0.0001), primary (p = 0.021), and secondary graft failure (p = 0.024). Carbapenem-resistant gram-negative bacteria were more common during recurrent BSI episodes (23.7% vs. 6.0%; p = 0.003). In only 17.5% patients experiencing recurrent BSI episode and in only 3.9% of patients with at least one BSI episode phenotypically identical recurring pathogen was isolated. Conclusions: In view of low rate of recurrent BSI due to identical pathogen, empirical antimicrobial therapy should not be based on data on previous BSI episodes.